Relationship of light scatter change and Cdc42‐regulated actin status. Issue 6 (3rd July 2015) - Hong, Lin; Chavez, Stephanie; Smagley, Yelena; Chigaev, Alexandre; Sklar, Larry A.
Abstract : Background: Cdc42 GTPase has important roles in regulating intracellular actin reorganization. The current methods to monitor actin changes are typically complex and point by point. Methods: The effects of Cdc42 inhibitors on the side scatter changes were tested in a newly developed continuous assay using the flow cytometer. Staining with fluorescently labeled phalloidin was used for comparison. Results: Cdc42‐specific inhibitors caused dose‐dependent changes of both the right‐angle side scatter and the phalloidin‐stained actin. Conclusions: The right‐angle light scatter change can be used as a method to circumvent phalloidin staining and be an early convenient step in screening Cdc42 inhibitors. © 2015 International Clinical Cytometry Society